Evaluation of a Novel Method of Fuze Programming Based on the Number of Projectile Own Revolutions - Grzegorz JĄCZEK (Ocena nowatorskiej metody programowania zapalników liczbą obrotów własnych pocisku, 2022)
This paper presents an innovative method of programming fuzes for airburst munitions based on the principle of counting the number of revolutions a projectile makes around its centre line along the flight trajectory in order to determine the distance travelled by the projectile. The proposed innovative method of fuze programming was compared to other known methods of fuze programming based on the results of a computer simulation of firing a 40 mm grenade launcher under near-real conditions. For this purpose, a methodology was developed for external ballistic calculations using a mathematical model of the three-dimensional motion of a non-deformable flying object considered to be a rigid body with six degrees of freedom in an ISO 1151 coordinate system. Simulations were carried out taking into account real firing conditions for 40 mm grenade launcher ammunition armed with fuzes programmed by each of the methods evaluated. Targets located at various distances were fired upon and the level of dispersion of real fuze action points relative to the expected fuze action point was evaluated for each programming method. It was concluded that the method of determining the distance travelled by the projectile with the principle of counting the projectile’s revolutions under real conditions resulted in a dispersion of the fuze action points greater than with the time based methods. In conclusion it was observed that the method of determination for the revolving projectile based on counting the projectile’s rotations along the flight trajectory did not guarantee the required precision of the fuze action point locations. This means that the application of the methods to determine the distance of projectile burst along the flight trajectory did not increase the effectiveness of airburst fragmentation munitions.
Keywords: Nowatorska metoda programowania zapalników